ISOLASI DAN KARAKTERISASI Phytophthora palmivora PENYEBAB PENYAKIT BUSUK AKAR DAN BATANG PADA DURIAN - Alberida, Heffi; Sunarwati, Diah; Yoza, Retra (Sainstek : Jurnal Sains dan Teknologi, 2010)
Isolation and characterization of fungus that caused root and stem rotten in durian have been conducted. Isolation using baiting method with apple and than inoculated to PSM medium, while characterization using light microscope. Characterization result showed that P. palmivora isolated from infected durian have white, stratified and stellate colony, unsepta hyphae and form clamidospore, oospore, zoospore and sporangium.Key words: isolation, Phytophthora palmivora, spora